Hennes & Mauritz (H&M). standing up for human rights in China / B : - Derr, Timothy, (SAGE business cases., 2021)
H&M emphasises their dedication to ethical purchasing while simultaneously expressing a firm long-term commitment to China. By making this declaration, H&M intends to mend its ties with China and reestablish mutual respect and cooperation. How will H&M continue its business links with China if the accusations are true and Xinjiang cotton is irreversibly polluted by forced labour?